Trimodality treatment of malignant pleural mesothelioma - (:unkn) unknown (LIPPINCOTT WILLIAMS & WILKINS, 2008)
Introduction: Multimodality treatment has achieved significant success in local control and treatment of early-stage malignant pleural mesothelioma patients. However, its favorable effect on survival is questionable. Methods: We have instituted a trimodality treatment protocol consisting of extrapleural pneumonectomy, adjuvant high-dose (54 Gy) hemithoracic irradiation, and platin-based chemotherapy in a multiinstitutional setting. Preoperative pulmonary function tests, echocardiogram, chest computed tomography, and magnetic resonance imaging scans were performed in all patients. Twenty patients have been treated with this protocol during 2003-2007. Seventeen had a history of environmental asbestos/erionite exposure. Clinical stages were T1-3N0-2. Results: Median age was 56 (41-70, 8 female). There was one postoperative mortality (% 5) due to ARDS. Morbidity occurred in 11 patients (% 55). Histology was epithelial in 17, mixed in 2, and sarcomatoid in 1. Sixteen patients underwent extrapleural pneumonectomy. Microscopic margin positivity was present in 14 patients with macroscopic complete resection. Twelve patients completed all three treatments. Median follow-up was 16 months (1-43). Overall median survival was 17 months (24% at 2 years). Eight patients had extrapleural lymph node involvement (internal mammary [n = 3], subcarinal [n = 2], pulmonary ligament [n = 1], diaphragmatic [n = 1], subaortic [n = 11]. There was better survival in patients without lymph node metastasis (24 versus 13 months median survival, p = 0.052). Currently, 7 patients are alive, 6 without recurrence, and 2 patients at 40 and 45 months. Conclusions: Trimodality treatment in malignant pleural mesothelioma seems to prolong survival in patients without lymph node metastasis. Novel techniques are needed for preoperative assessment of extrapleural lymph nodes.
Keywords: malignant pleural mesothelioma; extrapleural pneumonectomy; high-dose hemithoracic irradiation; adjuvant chemotherapy; PHASE-II TRIAL; EXTRAPLEURAL PNEUMONECTOMY; HEMITHORACIC RADIATION; INDUCTION CHEMOTHERAPY; THERAPY; RADIOTHERAPY; RESECTION; PLEURECTOMY/DECORTICATION; PATTERNS; DISEASE